Evaluation of green building rating systems for Egypt - Karmany, HebaAlla Mostafa (AUC Knowledge Fountain, 2015)
The average life of most structural types of buildings is fifty years. This projected lifespan will accordingly have an impact not only on the current inhabitants but also on the future generations. Therefore, nowadays, the subject of environmental conditions, and how our actions affect it, is of considerable consideration. The Egyptian economy was previously dependent on the agricultural, industrial, and transportation sector. Today, the construction industry plays an important role in the economic growth of the country, which is the key to developing our quality of life. Despite the difficult conditions and political instability facing Egypt in the last four years, the construction sector attained a growth of over 5% in 2013 against 3.3% in 2012 (Central Bank of Egypt-Egypt Economic Report). According to Egypt’s Vision 2030: Sustainable Development Strategy; it is forecasted that the population in Egypt will reach to 140 million by 2050; which will consequently necessitate an increase in the percentage of the planning and built-up areas leading to the use of more construction sites, land areas to cover this alarmingly rapid demographical increase. In parallel, there will be more demand for materials, energy, and water resources to accommodate this fast growth in population and urban growth. Additionally, buildings contribute significantly to the amount of disposed municipal, and construction and demolition waste. Consequently, there is an urgent need to provide guidelines and strategies for the development of the construction sector as a catalyst to green building. Thus, the various developed green building rating systems worldwide such as Leadership in Energy and Environmental Design (LEED) and Building Research Establishment Environmental Assessment Methodology (BREEAM) in order to assess the potential impacts of the building on the environment, economy and society, play a vital role in defining the level of sustainability in the construction industry. This research evaluates various green building rating systems through a quantitative and qualitative comparative analysis. The basis of this analysis was on an explicit criteria framework. The assessed rating systems are: Building Research Establishment Environmental Assessment Methodology New Construction (BREEAM NC 2014); Comprehensive Assessment System for Built Environment Efficiency (CASBEE 2014) for Building New Construction; Excellence in Design for Greater Efficiencies by the International Finance Corporation (EDGE IFC) Homes v1.1, Pearl Rating System (PRS) Design and Construction by ESTIDAMA v1.0; Green Pyramid Rating System NC (GPRS); Global Sustainability Assessment System Building Typologies (GSAS v2.0); Leadership in Energy and Environmental Design NC (BD and C) (LEED v4.0); and TARSHEED Residential v1.0. The selection of rating systems relied on an explicit criterion. The next phase included the selection of a case study (new construction) in order to measure its performance using three rating systems, namely, LEED, TARSHEED, and GPRS. The outcome of this research is a set of recommendations to Egypt Green Building Council committee for the development of future versions TARSHEED rating system.